EBV latent membrane protein-1 protects B cells from apoptosis by inhibition of BAX - Naschberger, Elisabeth; Stürzl, Michael; et al. (Blood, 2005)
Latent membrane protein 1 (LMP-1) of Epstein-Barr virus (EBV) promotes tumorigenesis by inhibiting apoptosis. We show that an important antiapoptotic activity of LMP-1 is the inhibition of Bcl2-associated protein X (Bax), a potent proapoptotic protein. BAX expression was regulated by LMP-1 activation of nuclear factor κB (NF-κB) via the C-terminal activation region 1 (CTAR-1) and CTAR-2. Interestingly, p65/p50 inhibited, whereas p50/p50 increased, BAX promoter activity as demonstrated by overexpression and selective inhibition of these NF-κB isoforms. Electrophoretic mobility shift analysis revealed that LMP-1 activates 2 of the 3 NF-κB binding sites (κB1-κB3) in the BAX promoter. LMP-1 induced binding of the NF-κB heterodimer p65/p50 to the κB2 site and of the p50/p50 homodimer to the κB3 site. Promoter mutation analysis revealed that the κB2 site is necessary for inhibition of BAX promoter activity and the κB3 site, for its activation. However, the activation of the BAX promoter by LMP-1 was observed only in the presence of specific inhibitors of p65/p50. In all other cases, LMP-1 inhibited BAX promoter activity. Most importantly, the antiapoptotic activity of LMP-1 was considerably decreased in cells deficient for BAX. These results indicate that the inhibition of Bax may be an important antiapoptotic activity of LMP-1. © 2005 by The American Society of Hematology.
Created from Fastlane, Scopus look-up